Discrimination and Psychosocial Well-Being of Migrants in Spain: The Moderating Role of Sense of Community - García-Cid, Alba; Gómez-Jacinto, Luis; Hombrados-Mendieta, Isabel; Millán-Franco, Mario; Moscato, Gianluigi (Frontiers in Psychology, 2020)
The discrimination migrants perceive during their adaptation process is one of the main sources of stress and it affects their well-being, health and integration severely. The present study analyses how the sense of community can have a protective effect against the perception of discrimination and its negative consequences by verifying the following theoretical model: discrimination predicts three indicators of psychosocial well-being (psychological distress, satisfaction with life and social exclusion feelings). Furthermore, the theoretical model proposed also considers the hypothesis that sense of community has a moderating role on the effect of perceived discrimination regarding the three variables mentioned above. 1714 migrants from Eastern Europe, Africa and Latin America who live in Malaga, Spain, participated in the study. Data were collected using random-route sampling and survey methodology. After carrying out multiple regression analyses, using the PROCESS tool in SPSS 20, the theoretical model was verified: sense of community reduces the negative effects of perceived discrimination for the variables psychological distress, satisfaction with life and social exclusion feelings. Therefore, migrants who have a greater sense of community experience less negative consequences, as compared to those with a lower sense of community, for whom the consequences of such variables are more negative. These results highlight the importance for migrants to rebuild social networks in the host country and develop a good sense of community. Results also allow the development of intervention patterns to favour positive interactions between native population and migrants.